1966
DOI: 10.1071/ch9660303
|View full text |Cite
|
Sign up to set email alerts
|

Eremophilane sesquiterpenes from Eremophila mitchelli

Abstract: 8α-Hydroxy-7α(H)-eremophila-1,ll-dien-9-one and 8α-hydroxy-7α(H)-eremophila-l0,ll-dien-9-one have been isolated from the wood oil of Eremophila mitchelli and their structure shown to be (I) and (11) respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

1969
1969
2013
2013

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…[14] The presence of unusual terpenoid metabolites with a ketone group became evident as early as 1932 with the isolation of eremophilone ketone and its oxygenated derivatives from the wood oil of E. mitchellii. [17,28,69] Subsequently, it was suggested that the skeleton, of what now has become known as the eremophilane type, arises by methyl migration in precursors possessing the isoprenoid skeleton and configuration of the normal and biosynthetically regular eudesmanes. [14] The presence of eudesmol has been established and three derivatives accumulate in E. scoparia.…”
Section: Cyclic Sesquiterpenesmentioning
confidence: 99%
See 4 more Smart Citations
“…[14] The presence of unusual terpenoid metabolites with a ketone group became evident as early as 1932 with the isolation of eremophilone ketone and its oxygenated derivatives from the wood oil of E. mitchellii. [17,28,69] Subsequently, it was suggested that the skeleton, of what now has become known as the eremophilane type, arises by methyl migration in precursors possessing the isoprenoid skeleton and configuration of the normal and biosynthetically regular eudesmanes. [14] The presence of eudesmol has been established and three derivatives accumulate in E. scoparia.…”
Section: Cyclic Sesquiterpenesmentioning
confidence: 99%
“…eremophilone (42) and eudesmane sesquiterpenes are dominant in only three species: E. mitchellii, E. scoparia and E. rotundifolia. [17,28,65,69,70] Two aromatic sesquiterpenes, (1R, 4R)-calamenene (60) and (1R, 4R)-7-hydroxy-calamenene (61) characterize the essential oils of E. drummondii and E. virens. [73,74] The unusual keto alcohol (+)-oplopanone (62) was isolated from E. miniata.…”
Section: Cyclic Sesquiterpenesmentioning
confidence: 99%
See 3 more Smart Citations